Normativity and ethics: the error in the error theory - Lofitis, Kipros (2019)
Do moral norms invariably supply agents with reasons? Does the dedicated immoralist necessarily have adequate reason to act morally? Ordinary thought may have it that the answers are yes and yes, but some people think no and no. The error theorist, in particular, thinks so on the grounds that all reasons, weak or strong, are instrumental: necessarily favouring actions that are instrumental to the agent’s own ends. For this reason, she is inclined to impute ordinary thought with error. This thesis examines the error theorist’s grounds for thinking this, and finds none convincing. The resulting conclusion is that — for all we know — moral norms do invariably supply agents with reasons, and that the error theorist herself errs in thinking that they do not. The thesis closes by considering an alternative route to supporting the claim that moral norms do not invariably supply agents with reasons, which even though is rather attractive, is also in dire need of support.